PROTECTIVE ROLE OF VITAMIN C AND E AGAINST SODIUM ARSENATE INDUCED CHANGES IN DEVELOPING KIDNEY OF ALBINO MICE - Qureshi, Fariha; Tahir, Mohammad; Sami, Waqas (Journal of Ayub Medical College Abbottabad, 2009)
Background: Arsenic is a teratogenic agent present in the environment as oxides and arsenate and humans are exposed to it through contaminated drinking water, food, soil and air. This investigation was undertaken to evaluate protective role of Vitamin C and E against teratogenic injury produced by sodium arsenate in developing kidney of the mouse. Methods: Twenty-four pregnant albino mice of BALB/c strain, were randomly divided into 4 groups of 6 each: A1, A2, A3 and A4. Group A1 served as the control and received weight related distilled water by intra-peritoneal (I/P) injection, group A2 was given a single doses of 35 mg/kg on 8th GD whereas groups A3 and A4 were treated with Vitamin C and E by IP injection, 9 mg/kg/day and 15 mg/kg/day respectively, starting from 8th day and continued for the rest of the pregnancy period. The foetal kidneys were weighed and histological studies carried out including micrometry on different components of nephron. Results: Sodium arsenate toxicity manifested as an increase in weight of the kidneys, wider nephrogenic zone and significant reduction in the mean of number of mature renal corpuscles as compared to the control group (p<0.000). There were moderate to severe necrotic and degenerative changes in proximal and distal convoluted tubules; glomeruli were hypercellular, the Bowman’s spaces were obliterated. There was a statistically significant difference in mean diameter of renal corpuscles of group A2 when compared with groups A1, A3 and A4, (p<0.000). Conclusions: The findings implied that groups receiving Vitamin C and E along with sodium arsenate showed an overall improvement in all parameters, indicating the protective role of Vitamin C and E against arsenic induced teratogenicity in developing kidney and are safe to use during pregnancy without deleterious effect on human conspectuses in arsenic exposed areas. Keywords: Arsenic, teratogenic, ascorbic acid, nephrogenesis.